Efficacy and Safety of Recombinant Human Adenovirus Type 5 (H101) in Persistent, Recurrent, or Metastatic Gynecologic Malignancies: A Retrospective Study - Zhang, Jing; Zhang, Qiying; Liu, Zi; Wang, Juan; Shi, Fan; Su, Jin; Wang, Tao; Wang, Fei (Frontiers in Oncology, 2022)
Background To assess the efficacy and safety of recombinant human adenovirus type 5 (H101) in patients with persistent, recurrent, or metastatic gynecologic malignancies. Methods The study retrospectively enrolled patients with persistent/recurrent/metastatic gynecologic malignancies who received H101-containing treatment at The First Affiliated Hospital of Xi’an Jiaotong University from September 1, 2019 to September 30, 2021. H101 was injected intratumorally into target lesions and dosage was calculated based on tumor diameter once a day for five consecutive days. The primary endpoint was local control (LC) rate. Secondary endpoints included objective response rate (ORR), duration of response (DOR) and progression-free survival (PFS). Safety was the exploratory endpoint. Depending on prior treatment, patients received H101 either as monotherapy or as a combination therapy. Results Totally, 29 patients were enrolled in the study. Median follow-up was 6.3 months (range: 3.2-27.9) from data analysis cut-off on December 31, 2021. The LC rate at 3 months was 44.8%, while ORR was 72.4%. Median DOR and PFS rates were not determined. The DOR rate, PFS rate at 6 and 12 months were 88.1%, 74.6% and 70.5%, 62.2%, respectively. Responses were observed in all four cancer types. Most treatment-related adverse events (90.5%) were grade 1 or 2, with the most common being fever (70%). Clinically significant adverse events were uncommon (7.9% in grade 3 and 1.6% in grade 4). No treatment-related deaths occurred. Conclusion Our study showed that H101 (either monotherapy or combination therapy) has promising efficacy and favorable safety in patients with persistent, recurrent, metastatic gynecologic malignancies.